The Influence of Transformational Leadership on Creative Performance Mediated by Trust in Supervisor at PT Pertamina Hulu Rokan - Muzzamir; Rahmat, Adi; Dwika Listihana, Wita (SAINS ORGANISASI, 2023)
The aim of this research is to examine the influence by analyzing the impact of Transformational Leadership on Creative Performance, mediated by Trust In Supervisor, at Pertamina Hulu Rokan. The population in this study comprises all employees working in the Field Operations Department in Duri, totaling 60 employees, with a sample size of 59 respondents. Data collection was conducted using a questionnaire distributed through Google Forms. The data analysis technique employed in this research is Structural Equation Modeling (SEM), utilizing SmartPLS 3.0 as the data processing tool. The results of this study indicate that Transformational Leadership has a significant direct impact on the Creative Performance of employees in the Field Operations Department at PT. Pertamina Hulu Rokan. Transformational Leadership also has a significant direct impact on Trust in Supervisor for employees in the same department. The Trust in Supervisor variable also has a significant direct impact on the Creative Performance of employees in the Field Operations Department. The research findings also reveal that Trust in Supervisor is capable of mediating the relationship between Transformational Leadership and Creative Performance of employees in the Field Operations Department at PT. Pertamina Hulu Rokan. This implies that the better the Trust in Supervisor, the more it will influence the relationship between Organizational Support Perception and Creative Performance